The Association between Hallux Valgus and Proximal Joint Alignment in Young Female Dancers - Steinberg, N.; Siev-Ner, I.; Zeev, A.; Dar, G. (International Journal of Sports Medicine, 2015)
Very little is known about the relationship between proximal joint alignment and hallux valgus among young dancers. This study sought to determine the extent to which spinal and lower extremity alignments are involved in hallux valgus, and to identify predicting variables for its development in young dancers. A group of 1 336 young female dancers aged 8–16 years, and 226 control participants of the same age cohort were screened for the presence of hallux valgus, body physique characteristics, joint range of motion, and anatomical anomalies. Hallux valgus was common in the 2 young female populations studied. Among the dancers, 40.0% had bilateral hallux valgus and 7.3% unilateral. Among the controls, 32.3% had bilateral and 1.8% unilateral hallux valgus (χ2=8.27, df=1, p=0.004). Following logistic regression analysis, age (OR=1.028, 95% CI=0.968-1.091), genu varum (OR=1.514; CI=1.139–2.013) and scoliosis (OR=2.089; CI=1.113–3.921) were found to be significant predicting factors for hallux valgus in the dancer group, whereas in the control group, the predicting factors were age (OR=0.911, 95% CI=0.801–1.036) and ankle plantar flexion range of motion (OR=0.972; CI=0.951–0.992). In conclusion, it was found that spinal deformity, lower extremity alignment, and joint range of motion are strongly related to hallux valgus.
Keywords: dancers; hallux valgus; ROM; scoliosis; lower extremity alignment